An Analysis of Students’ Problems in Reading Comprehension at SMK Negeri 1 Gorontalo - Ariani Prihatmini Pakaya; Rasuna Rasid Talib; Sri Rumiyatiningsih Luwiti; Sartin T. Miolo; Rahmawaty Mamu (Transbahasa, 2026)
This study aimed to identify and thoroughly analyze the specific reading comprehension problems faced by tenth-grade vocational students at SMK Negeri 1 Gorontalo within the implementation of Kurikulum Merdeka. The research employed a descriptive qualitative methodology utilizing the interactive data analysis model framework. The participants consisted of 21 tenth-grade vocational students (Batch 2023). Data were collected using a 42-item Likert-scale diagnostic questionnaire administered via Google Forms, complemented by semi-structured interviews with 10 selected key respondents. The theoretical foundation was grounded in Duke and Cartwright's Active View of Reading model. The findings revealed a severe